2000
DOI: 10.1093/nar/28.18.3666
|View full text |Cite
|
Sign up to set email alerts
|

Human RNA lariat debranching enzyme cDNA complements the phenotypes of Saccharomyces cerevisiae dbr1 and Schizosaccharomyces pombe dbr1 mutants

Abstract: The cDNA encoding the human RNA lariat debranching enzyme (hDBR1) was identified and cloned by searching the Expressed Sequence Tag (EST) database and screening a HeLa cDNA library, based on predicted amino acid sequence homologies with the Saccharomyces cerevisiae, Schizosaccharomyces pombe and Caenorhabditis elegans debranching enzymes. The hDBR1 cDNA expressed in Escherichia coli showed debranching activity in vitro and was also shown to be functional in an interspecies specific complementation experiment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…For guide snoRNA processing in mammals, snoRNAs are transcribed as a part of the host gene introns. After being spliced, the excised introns are debranched by DBR1, and linearized introns are processed from both ends by exonucleases (22,34). The snoRNA region of the intron is bound by several snoRNP proteins, which protect it from degradation (10,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For guide snoRNA processing in mammals, snoRNAs are transcribed as a part of the host gene introns. After being spliced, the excised introns are debranched by DBR1, and linearized introns are processed from both ends by exonucleases (22,34). The snoRNA region of the intron is bound by several snoRNP proteins, which protect it from degradation (10,50).…”
Section: Discussionmentioning
confidence: 99%
“…7B). RNA bands a and b were recovered from the denaturing gel and subjected to debranching with recombinant hDBR1 (22). Flag-tagged hDBR1 proteins, which were detectable by antiFlag antibody, were recovered from transfected HEK293T cells by use of anti-Flag M2 resin (Fig.…”
Section: Identification Of Rnas That Associate With Drosha During Cromentioning
confidence: 99%
“…Similarly, more distantly related enzymes, such as the mRNA-capping enzymes, mRNA 5Ј-triphosphatases (cluster 9) (Changela et al 2001), acid sphingomyelinase-like phosphodiesterases (cluster 8) (Testi 1996), RNA lariat debranching enzyme (Kim et al 2000), CD73-5' nucleotidase (Airas et al 1997), and MRE11A (Hopfner et al 2001) were all identified as containing protein phosphatase domains. Within the protein kinases, the guanylyl cyclases were also identified (cluster 5) (Lucas et al 2000).…”
Section: Misclassifications and Related Gene Families Detected By Trimentioning
confidence: 99%
“…The intron is then processed by exonucleolytic cleavage of the 39-lariat tail and linearization by the debranching enzyme Dbr1 ( Fig. 1D; Kim et al 2000;Cheng and Menees 2011). The spliceosome is disassembled and recycled (Arenas and Abelson 1997;Martin et al 2002).…”
mentioning
confidence: 99%